Ontologi Sains Modern: Fondasi Filsafat Di Balik Pengetahuan Ilmiah - Ayu Putriana Dewi; Enjelika Enjelika; Agung Winarno (Pusat Riset dan Inovasi Nasional, 2024)
Science is considered a theory of understanding the universe that uses philosophical foundations to determine what counts as reality, based on empirical findings. The main objective in this study is to identify how the ontology of science forms the basis of scientific theory, whether in physics, biology, or social sciences, and how it relates to recent developments in technology and scientific research. Based on this research, it seeks to explain the ontology of modern science in terms of the philosophical foundations behind scientific knowledge. Philosophy of science, ontology, and science are intertwined in the effort to understand reality. In the modern era, the main challenge in philosophy and ontology is to maintain the essence of human existence in the face of rapid technological developments, such as the metaverse. Critical efforts are needed to maintain a balance between technology and human values.